2022
DOI: 10.1089/whr.2021.0119
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Changes in Body Composition During the Menopausal Transition and Relation to Cardiovascular Risk: A Contemporary Review

Abstract: The menopausal transition period in aging women is strongly associated with weight gain. Evidence shows that weight changes during menopause increases the risk of developing cardiovascular disease (CVD) in postmenopausal women. However, the potential mechanisms that cause weight gain and adverse changes to body composition specifically during the menopausal transition period remain to be elucidated. In this contemporary review, we examined recent evidence for adverse changes in body composition at midlife duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 49 publications
(70 reference statements)
1
16
0
1
Order By: Relevance
“…Concomitant cardiovascular and metabolic complications may further disrupt sexual function in women and induce a decrease of arousability, orgasm and satisfaction in acromegaly (60). On the other hand, the estrogens fall spontaneously occurring with the onset of menopause leading to a state of physiologic hypogonadism, is known to promote a cardiometabolic transition leading to obesity, metabolic syndrome, diabetes mellitus, arterial hypertension, and cardiovascular disease, commonly seen also in women with acromegaly (96)(97)(98). In the current study, elderly patients reported lower FSFI total and all domain scores, and the prevalence of sexual dysfunction was higher in patients with long disease duration and/or older than 64 years as compared to younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant cardiovascular and metabolic complications may further disrupt sexual function in women and induce a decrease of arousability, orgasm and satisfaction in acromegaly (60). On the other hand, the estrogens fall spontaneously occurring with the onset of menopause leading to a state of physiologic hypogonadism, is known to promote a cardiometabolic transition leading to obesity, metabolic syndrome, diabetes mellitus, arterial hypertension, and cardiovascular disease, commonly seen also in women with acromegaly (96)(97)(98). In the current study, elderly patients reported lower FSFI total and all domain scores, and the prevalence of sexual dysfunction was higher in patients with long disease duration and/or older than 64 years as compared to younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…Aging is strongly associated with weight gain related to the accumulation of body fat depot during a lifetime. The adverse changes in body composition accelerate in women during the menopausal transition [ 4 ]. The age-associated decline in physical capacity related among others to the decrease in especially appendicular skeletal muscle mass [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, women in one group (the metabolic group) were approximately three years older than the non-metabolic group, but the participants’ menopausal status was not examined [ 73 ]. The menopausal transition period in aging women is strongly associated with weight gain [ 74 ].…”
Section: Resultsmentioning
confidence: 99%